Get started with Distributed Tracing - Deza, Alfredo; Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
Learn all about distributed tracing in this 1 hour course. If you want to go beyond logging and monitoring, and trying to tell a story by connecting the dots, then distributed tracing is the way to go. Topics include: * Opentracing and the foundations of distributed tracing libraries like Jaeger * Micro-service strategies and other microservice implementations that make distributed-tracing a perfect use case * Implement distributed tracing instrumentation in a Github project using docker compose with multiple Docker containers * Leverage the knowledge to use hosted services like Datadog for querying and debugging traces.